Praktik Jual Beli Ayam - Vepri Anti Siregar; Nurhotia Harahap (IAIN Padangsidimpuan, 2022)
Muamalah is carried out on the basis of considerations of bringing benefits and avoiding harm in people's lives. Muamalah is carried out by maintaining the value of justice, avoiding elements of persecution, avoiding elements of taking opportunities in narrowness. In buying and selling honesty and truth are the most important values. Islam forbids fraud in all human activities, including in business activities and buying and selling. buying and selling carried out by the Simardona village community, Batang Onang District, North Padang Lawas Regency where the seller, as it is often seen, is that in the markets the seller of chicken pieces uses a sitting scale so that every sale of chicken pieces is easily weighed and so that it is clearly seen by the buyer the weighing process. Chicken sellers in Simardona Village, Batang Onang District, North Padang Lawas Regency, sell live chickens, not slaughtered. Chicken sellers only catch live chickens and then state the price to the buyer and in fact the chicken sellers in Simardona Village, Batang Onang District, North Padang Lawas Regency when selling chickens, the chickens are not weighed first, even the chicken sellers do not know how much the chicken will be selling. On the one hand, the seller sees that the chickens that he is about to sell already look big in size and in fact it often happens that the body size of the chicken which is covered with chicken feathers does not match the chicken that has been cleaned or slaughtered.